Effectiveness of Brochures in Improving the Knowledge of PKK Mothers in South Danguran on Self-Medication Drug Use and Disposal - Ismah Rahmadhani; Nur Atikah; Dwi Subarti (Jurnal Ilmiah Medicamento)
Limited health knowledge increases the risk of improper use and disposal of self-medication drugs. Educational interventions, such as brochures, are expected to enhance public awareness. This study aimed to evaluate the effectiveness of brochures in improving the knowledge of PKK (Family Empowerment and Welfare) mothers in RT 01 RW 10, South Danguran, regarding the appropriate use and disposal of self-medication. A pre-experimental one-group pre-test–post-test design was employed, involving 37 purposively selected respondents who met the inclusion and exclusion criteria. Univariate analysis was used to describe respondent characteristics, knowledge levels, and survey responses, while bivariate analysis was performed using the Wilcoxon signed-rank test. The results showed that most respondents were aged 46–65 years (64.9%), had a high school education (56.8%), and worked as housewives or laborers (67.6%). Before the intervention, 51.4% of respondents had a moderate level of knowledge, whereas after the intervention, 81% demonstrated a good level of knowledge. The Wilcoxon signed-rank test indicated a significant improvement, with a p-value of <0.001 (p < 0.05). In conclusion, brochures were effective in increasing knowledge regarding the use and disposal of self-medication drugs among PKK mothers in RT 01 RW 10, South Danguran.